Antiproliferative effects of pomegranate extract in MCF‐7 breast cancer cells are associated with reduced DNA repair gene expression and induction of double strand breaks. Issue 6 (28th January 2013) - Shirode, Amit B.; Kovvuru, Prasad; Chittur, Sridar V.; Henning, Susanne M.; Heber, David; Reliene, Ramune
Abstract Pomegranate extract (PE) inhibits the proliferation of breast cancer cells and stimulates apoptosis in MCF‐7 breast cancer cells. While PE is a potent antioxidant, the present studies were conducted to examine the mechanisms of action of PE beyond antioxidation by studying cellular and molecular mechanisms underlying breast tumorigenesis. PE inhibited cell growth by inducing cell cycle arrest in G2/M followed by the induction of apoptosis. In contrast, antioxidants N‐acetylcysteine and Trolox did not affect cell growth at doses containing equivalent antioxidant capacity as PE, suggesting that growth inhibition by PE cannot solely be attributed to its high antioxidant potential. DNA microarray analysis revealed that PE downregulated genes associated with mitosis, chromosome organization, RNA processing, DNA replication and DNA repair, and upregulated genes involved in regulation of apoptosis and cell proliferation. Both microarray and quantitative RT‐PCR indicated that PE downregulated important genes involved in DNA double strand break (DSB) repair by homologous recombination (HR), such as MRE11, RAD50, NBS1, RAD51, BRCA1, BRCA2, and BRCC3. Downregulation of HR genes correlated with increased levels of their predicted microRNAs (miRNAs), miR‐183 (predicted target RAD50) and miR‐24 (predicted target BRCA1), suggesting that PE may regulate miRNAs involved in DNA repair processes. Further, PE treatment increased the frequency of DSBs. These data suggest that PE downregulates HR which sensitizes cells to DSBs, growth inhibition and apoptosis. Because HR represents a novel target for cancer therapy, downregulation of HR by PE may be exploited for sensitization of tumors to anticancer drugs. Copyright © 2013 Wiley Periodicals, Inc.